STRATEGI KEBERLANJUTAN BISNIS COFFEE SHOP A’ROBI DI TENGAH PERSAINGAN PASAR - Andri Alamsyah; Raihan Fatahillah; Indah veronika; Friscia Novianti Setiawan; Aulia Farida; Nuraisyah; Andi Maman Firmansyah; Fachrul Reza (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the sustainability strategies of Coffee Shop A’ROBI as a local MSME coffee business developing in Palu City, Central Sulawesi. Using a qualitative research method, the study explores internal and external factors influencing A’ROBI’s growth amid the rising trend of coffee consumption following the city’s recovery from the 2018 disaster. The findings indicate that A’ROBI’s strengths lie in its consistent flavor quality, affordable pricing, strategic locations, and comfortable atmosphere. However, the business faces weaknesses such as limited menu variation and operational management challenges. Business opportunities arise from the increasing popularity of coffee culture and potential collaborations, while threats include intense competition and shifting consumer preferences. Overall, A’ROBI is able to maintain its business sustainability through continuous product innovation and improved management practices.